2018
DOI: 10.13031/aea.12487
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Simulation-Based Optimization in Grafting Labor Allocation

Abstract: ABSTRACT. Vegetable grafting is a labor-intensive operation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…In addition, the implementation of DDDAS paradigm in this framework and the fidelity level optimization of the dynamic decision making is discussed here . The planning unit relies on the concept of simulation-based optimization where simulation mimics the performance of the system under study through the estimated parameters provided by the measuring unit, and optimization models look through different scenarios to find the optimal layout design ) and labour management (Masoud et al 2018). In this work, we will discuss the irrigation monitoring aspect which will finalize this DDDAS framework.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the implementation of DDDAS paradigm in this framework and the fidelity level optimization of the dynamic decision making is discussed here . The planning unit relies on the concept of simulation-based optimization where simulation mimics the performance of the system under study through the estimated parameters provided by the measuring unit, and optimization models look through different scenarios to find the optimal layout design ) and labour management (Masoud et al 2018). In this work, we will discuss the irrigation monitoring aspect which will finalize this DDDAS framework.…”
Section: Methodsmentioning
confidence: 99%
“…The simulated data includes the location of workers within the facility and the water consumption of the plants. The simulation models used in the DDDAS framework has been validated in these works (Masoud et al 2018;.…”
Section: Data Collectionmentioning
confidence: 99%
“…While, Shakibayifar et al 58 applied SBO technique to rescheduling train traffic in uncertain conditions during disruptions. Masoud et al 59 demonstrated the applicability of SBO in agriculture (horticultural nurseries).…”
Section: Literature Reviewmentioning
confidence: 99%